PENERAPAN ALGORITMA DIJKSTRA DALAM PERANCANGAN SISTEM INFORMASI PENCARIAN LAYANAN KESEHATAN DI RUMAH SAKIT - Zaky, Abdul; Putra, Akmal Darman; Nurhadi, Muhammad (Journal of Hospital Administration and Management (JHAM), 2023)
Technology plays a crucial role in supporting life in various aspects, including social, economic, and healthcare sectors within the community. The development of technology in the healthcare field covers several aspects, such as patient services, internal hospital information systems, hospital management, and patient information systems. Some hospitals have implemented online-based information systems for patients. Through these systems, patients can access information related to service schedules, service availability, and types of services offered. However, access to these systems remains limited, generally only available through hospital websites or kiosks located within the hospital. This still restricts patients from obtaining detailed information regarding service availability and travel distance to hospitals based on their specific needs and required treatments. Although travel distance information can already be accessed through various available applications, such information is not yet integrated with the availability of hospital services. Therefore, there is a need for a service and information system that patients can use in the form of an application providing integrated data on service availability and travel distance. The proposed application is Android-based and accessible to the general public, given that most people are already familiar with and capable of using this operating system. The application will provide several input fields that users can fill in, such as patient name, gender, age, address, and medical complaints. These inputs will be processed by the application system to provide information on hospitals that offer the services needed by the patient, along with the travel distance from the patient’s location to each service-providing hospital. The application will also display the fastest route from the patient's location to the selected hospital. The determination of the fastest route utilizes Dijkstra’s Algorithm. Dijkstra’s Algorithm is a mathematical algorithm widely used for optimizing problem-solving conditions. Several similar applications have been developed previously; however, those applications generally only provide information about healthcare locations and general routes in the area. This application, however, is more specifically developed to allow patients to simply input the required healthcare services and their current address or location, which the system will then quickly process to deliver the nearest healthcare solutions and the fastest route to reach them.